2004
DOI: 10.4172/plastic-surgery.1000385
|View full text |Cite
|
Sign up to set email alerts
|

The indications and reliability of vein graft use in free flap transfer

Abstract: BACKGROUND: Adequate recipient vessels are critical for free flap success. There are, however, situations in which the local recipient vessels are inadequate. In these situations, vein grafts are required to allow pedicle extension to recipient vessels. OBJECTIVES: To determine the indications, technique, reliability and outcome of vein graft use in free flap transfer. METHODS: A retrospective review of 198 consecutive free flaps by a single surgeon. RESULTS: Vein grafts were required in 9.6% of free flaps. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Another precaution needed in this technique is the preparation of the vein graft. Vein grafts are widely used in microsurgical reconstruction (Classen, 2004;Hwee et al, 2020;Jandali et al, 2016;Kang & Kim, 2019). However, long vein grafts should be avoided, especially in this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Another precaution needed in this technique is the preparation of the vein graft. Vein grafts are widely used in microsurgical reconstruction (Classen, 2004;Hwee et al, 2020;Jandali et al, 2016;Kang & Kim, 2019). However, long vein grafts should be avoided, especially in this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Despite concerns that vein grafts may increase the incidence of free flap thrombosis, 2,7 several studies have demonstrated that using vein grafts may not compromise overall flap success rates. 7,8 In this case series, arterial thrombosis leading to flap failure occurred in only one patient. The flap success rate and limb salvage rates in this series suggest that the possible risk of thrombosis posed by venous grafts should not preclude the use of this technique.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, one of two flaps that required unplanned vein grafting intraoperatively failed. 25 Despite a small sample size, the study reminds surgeons to plan for a potential vein graft.…”
Section: Vein Grafts By Locationmentioning
confidence: 98%